Trapezium With Quadrilateral

Geometry Level 4

In the figure, A F D AFD , B C D BCD and C F E CFE are straight lines. It is given that A B AB is parallel to E D ED , A B : E D = 5 : 7 AB : ED = 5 : 7 and B C : C D = 2 : 3 BC : CD = 2:3 . If the area of C D F \triangle CDF is 63 cm 2 63 \text{cm}^2 , then what is the area of A B C F ABCF ?


Source: Lingnan Secondary School Post-Mock Exam Paper.
Thanks to my student Chang Chi Kong for his contribution.
87 cm 2 87 \text{cm}^2 187 cm 2 187 \text{cm}^2 250 cm 2 250 \text{cm}^2 150 cm 2 150 \text{cm}^2

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Wing Tang
Mar 9, 2016

Let X 1 X_1 , X 2 X_2 , \cdots , X n X_n be the points on an R 2 \mathbb R^2 plane. In the following, we denote the area of an n n -sided polygon X 1 X 2 X n X_1X_2\cdots X_n by ( X 1 X 2 X n ) (X_1 X_2 \cdots X_n) .

Solution \textbf{Solution}

Let A B = 5 k AB=5k , D E = 7 k DE = 7k , B C = 2 h BC=2h and C D = 3 h CD = 3h for some positive constants h h and k k (as labelled in the figure).

In the figure, we construct a point G G on A D AD such that joining C G CG yields the result C G CG // B A BA . Then we have C G CG // D E DE . Now, it is readily seen that

( 1 ) C G F E D F , and ( 2 ) D A B D G C . \begin{aligned} &(1) & \triangle CGF &\sim \triangle EDF,\ \text{ and } \\ &(2) & \triangle DAB &\sim \triangle DGC. \end{aligned}

For (2), the proportionality of the corresponding sides gives C G = 3 k CG = 3k ; and then, for (1), it gives G F : D F = C G : E D = 3 : 7 GF : DF = CG : ED = 3:7 . Since C F G \triangle CFG and C F D \triangle CFD have the same height relative to their respective bases G F GF and D F DF , we have ( C G F ) = ( C D F ) G F D F = 63 × 3 7 = 27 cm 2 (CGF) = (CDF) \cdot \frac{GF}{DF} = 63 \times \frac{3}{7} = 27 \text{cm}^2 and so ( G C D ) = ( C D F ) + ( C G F ) = 63 + 27 = 90 cm 2 (GCD) = (CDF) + (CGF) = 63 + 27 = 90\ \text{cm}^2 .

For (2), we have ( A B D ) = ( G C D ) ( A B G C ) 2 = 90 ( 5 3 ) 2 = 250 cm 2 (ABD) = (GCD) \left(\frac{AB}{GC}\right)^2 = 90 \cdot \left(\frac{5}{3}\right)^2 = 250\ \text{cm}^2 .

Finally, we have ( A B C F ) = ( A B D ) ( C D F ) = 250 63 = 187 cm 2 (ABCF) = (ABD) - (CDF) = 250 - 63 = 187\ \text{cm}^2 . \Box

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...